Considerations on Mood Dysregulation Disorder (Research, Society and Development, 2023)
Introduction: Mood disorders encompass various clinical manifestations and require the establishment of specific diagnostic criteria, which is no different when analyzing Disruptive Mood Dysregulation Disorder (DHDD). Objective: The aim of this study was to evaluate the clinical, epidemiological and pathophysiological aspects of DHDD, building on knowledge based on case reports and established theoretical considerations. Materials and Methods: This is an integrative literature review on the general clinical characteristics of disruptive mood dysregulation disorder. The PICO strategy was used to develop the guiding question. In addition, the descriptors "Disruptive Disorder"; "Mood Disorders"; "Pathophysiology" were cross-referenced in the National Library of Medicine (PubMed MEDLINE), Scientific Electronic Library Online (SCIELO), Ebscohost, Google Scholar and Virtual Health Library (VHL) databases. Results and Discussion: The studies show that DHDD involves specific nuances within medicine, including historical, pathophysiological, clinical, epidemiological and therapeutic aspects. Conclusion: The diagnosis of DHDD was established recently, in 2013, by the DSM-V, following great concern about cases of misdiagnosis and the exposure of children and adolescents to the side effects of medication without real need. It is a medical condition that involves neural and biochemical alterations, evidenced by neuroimaging studies, and must be diagnosed based on specific criteria in order to establish an appropriate therapy.